DEVELOPMENT OF CARBON NANOTUBE-GRAPHENE COMPOSITE AS TRANSPARENT CONDUCTIVE ELECTRODE FOR GAN-BASED LED - KANG, CHUN HONG (2017)
Low dimensional sp2 carbon-based materials, i.e. carbon nanotube (CNT) and graphene, have attracted significant attentions to be used as transparent conductive electrode (TCE) for high performance GaN-based light-emitting diode (LED). This is largely motivated by several drawbacks associated with conventional indium tin oxide (ITO) film, e.g. chemical instability, scarcity in supply and brittleness unsuitable for flexible devices. To date, graphene has emerges as a promising replacement for ITO. However, significant improvements in the electrical and optical properties of graphene is deemed necessary in order to replace ITO. In this work, a fully-carbon composite made of CNT and graphene (CNT-graphene) is presented as TCE for GaN-based LEDs. In the initial stage, high quality single layer graphene was synthesized using chemical vapor deposition (CVD) method and transfer onto target substrate using optimized PMMA-based transfer techniques. By using similar techniques, a composite made of spin-coated CNT and CVD-grown graphene is prepared. The composite structure demonstrated low sheet resistance of ~533 / and about 88% of light transmittance when CVD-grown graphene was fused across the percolated network of CNTs. Higher average Hall-effect mobility was also observed as compared to pristine graphene and layer-by-layer stacking structures of CNTs on graphene or graphene on CNTs. By employing the composite film with a 2-nm-thin NiOx layer, the forward voltage of the device at 20-mA injection current is significantly reduced to 5.12 V. Simultaneously, about 4-fold improvement in light output power was also attained. This is attributed to the reduction of Schottky barrier height by NiOx layer and enhanced electrical pathway by fusing graphene across the CNT network, leading to superior carrier transport across the composite network on LEDs.